Effects of high nitrogen concentrations on ectomycorrhizal structure and growth of seedlings of Picea abies (L.) Karst - Brunner, Ivano (The New phytologist, 1995)
High nitrogen concentrations are known to affect ectomycorrhizal and ectomycorrhizal fungi in field and laboratory experiments. Using NH/ as a nitrogen source in the growth pouch system, a variety of structural modifications were documented on first order lateral roots of Picea abies (L.) Karst. seedlings. Root cells increased in size and number at high levels of NH4 + resulting in a hypertrophic appearance of roots in both uncolonized seedlings and in those inoculated with mycelia of the ectomycorrhizal fungus Hebeloma crustuliniforme (Bull, ex St. Amans) Quel. A fungal mantle surrounded short roots of inoculated seedlings, and the outer walls of epidermal and cortical cells were often thickened when in contact with fungal hyphae. No Hartig net developed, although intracellular penetration of fungal hyphae into epidermal and cortical cells frequently occurred. At moderate NH4 + concentrations, Hartig net development was incomplete, but occasional intracellular penetration of Hartig net hyphae into epidermal and cortical cells occurred. The addition of high levels of NH4 + after ectomycorrhizal development resulted in ectomycorrhizas with distinctly altered apical structures. None of the various NH4 + concentrations resulted in significantly different plant dry weights after two months of exposure, either with or without fungal inoculation. After four months, dry weight, root length and branching indices were higher in both inoculated plants and those exposed to high nitrogen. The root/shoot ratio and number of short roots per seedling were high with fungal inoculation. Shoot nitrogen levels after two and four months and the Ca levels after 4 months were higher with increasing NH4 + in the nutrient solution. Other mineral elements were not influenced by nitrogen concentrations and fungal inoculation